2013
DOI: 10.1155/2013/610950
|View full text |Cite
|
Sign up to set email alerts
|

Nutritionally Mediated Oxidative Stress and Inflammation

Abstract: There are many sources of nutritionally mediated oxidative stress that trigger inflammatory cascades along short and long time frames. These events are primarily mediated via NFκB. On the short-term scale postprandial inflammation is characterized by an increase in circulating levels of IL-6 and TNF-α and is mirrored on the long-term by proinflammatory gene expression changes in the adipocytes and peripheral blood mononuclear cells (PBMCs) of obese individuals. Specifically the upregulation of CCL2/MCP-1, CCL3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 86 publications
(105 reference statements)
1
121
0
Order By: Relevance
“…It was suggested that GPR84 acts as a proinflammatory receptor linking fatty acid metabolism to immunological res ponses (34)(35)(36). Other fatty acids such as arachidonic acid and saturated fatty acids have been demonstrated to increase proinflammatory IL-8 along with numerous other inflammatory factors, including IL-6, TNF-α, IL-1β and CXCL1 (37). Agonists of GPR84 were shown to amplify IL-8 production by PMNs, and GPR84 agonists work as chemo-attractants to both PMNs and macrophages (38).…”
Section: Factor Analysis Identified Cinc1-3 Mip-1/3` Mig Rantes Anmentioning
confidence: 99%
“…It was suggested that GPR84 acts as a proinflammatory receptor linking fatty acid metabolism to immunological res ponses (34)(35)(36). Other fatty acids such as arachidonic acid and saturated fatty acids have been demonstrated to increase proinflammatory IL-8 along with numerous other inflammatory factors, including IL-6, TNF-α, IL-1β and CXCL1 (37). Agonists of GPR84 were shown to amplify IL-8 production by PMNs, and GPR84 agonists work as chemo-attractants to both PMNs and macrophages (38).…”
Section: Factor Analysis Identified Cinc1-3 Mip-1/3` Mig Rantes Anmentioning
confidence: 99%
“…Th us, the fi ndings of a recent study (Gregson, Drust, Atkinson, & Salvo, 2010) indicate that match-to-match variability in performance characteristics of elite soccer players is high. Moreover, many factors within the body can infl uence muscle damage, such as infl ammation (Stoner et al, 2013), nutrition (Muñoz & Costa, 2013), intake of supplements (Goldfarb, 1999;Goldfarb, Garten, Cho, Chee, & Chambers, 2011). A signifi cant increase in muscle damage markers (Andersson, Ekblom, & Krustrup, 2008;Ascensão et al, 2008;Ispirlidis et al, 2008;Magalhães et al, 2010) has been described immediately aft er "friendly" soccer matches and throughout the post-match recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The current results showed that by prolonging consumption of TPC 35 oil, the level of 8-isoprostane increased. Oxidative stress is proposed as a stimulatory factor in increasing inflammatory mediators (30). Accordingly, at the end of the study, IL-1β in the TPC 35 group was higher than the other groups.…”
Section: Discussionmentioning
confidence: 83%